Lsi2: A black box in plant silicon transport - Coskun, Devrim; Deshmukh, Rupesh; Shivaraj, S. M.; Isenring, Paul; Belanger, Richard R. (Plant and Soil, 2021)
Background Silicon (Si) is widely considered a non-essential but beneficial element for higher plants, providing broad protection against various environmental stresses (both biotic and abiotic), particularly in species that can readily absorb the element. Two plasma-membrane proteins are known to coordinate the radial transport of Si (in the form of Si(OH)(4)) from soil to xylem within roots: the influx channel Lsi1 and the efflux transporter Lsi2. From a structural and mechanistic perspective, much more is known about Lsi1 (a member of the NIP-III subgroup of the Major Intrinsic Proteins) compared to Lsi2 (a putative Si(OH)(4)/H+ antiporter, with some homology to bacterial anion transporters). Scope Here, we critically review the current state of understanding regarding the physiological role and molecular characteristics of Lsi2. We demonstrate that the structure-function relationship of Lsi2 is largely uncharted and that the standing transport model requires much better supportive evidence. We also provide (to our knowledge) the most current and extensive phylogenetic analysis of Lsi2 from all fully sequenced higher-plant genomes. We end by suggesting research directions and hypotheses to elucidate the properties of Lsi2. Conclusions Given that Lsi2 is proposed to mediate xylem Si loading and thus root-to-shoot translocation and biosilicification, it is imperative that the field of Si transport focus its efforts on a better understanding of this important topic. With this review, we aim to stimulate and advance research in the field of Si transport and thus better exploit Si to improve crop resilience and agricultural output.
Keywords: Efflux; Lsi2; Membrane transport; Root-to-shoot translocation; silicon; Xylem loading